ANALISIS NILAI PASAR WAJAR SAHAM PT BANK TABUNGAN PENSIUNAN NASIONAL TBK DALAM RANGKA RIGHT ISSUE TAHUN 2010 - , Rennie Kameswara; , M. Edhie Purnawan, M.A., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In strengthening firmâs capital structure and expanding firmâs business, PT Bank Tabungan Pensiunan Nasional Tbk (BTPN) has conducted a corporate action through Right Issue I on December 2010. The purpose of this research is to analyze the fair market value of the Right Issue offering price. The fair market value in this research is obtained by using discounted cash flow-cash flow to equity model and relative valuation with application of PER (Price to Earning Ratio) and PBV (Price to Book Value) multiples. This research also uses the economic forecasting approach based on time series data namely technical analysis, by using Vector Autoregression model as a tool to forecast the stock price of BTPN. The fair market value of BTPN can be used by firm as a reference in determining the share price that will be offered to the public. It also can be used by investor in evaluating whether the pricing of BTPN is overvalued or undervalued. For this study, the data observed using discounted cash flow-cash flow to equity model and relative valuation are five financial statements and other information contained in the annual report of BTPN for period 2005 to 2009, financial statement in 2010 (quarter III) of BTPN and prospectus 2010 of BTPN, financial statements in 2010 (quarter III) of the comparable companies